Are adolescent elite athletes less psychologically distressed than controls? A cross-sectional study of 966 Norwegian adolescents - Rosenvinge,Janos; Sundgot-Borgen,Jorunn; Pettersen,Gunn; Martinsen,Marianne; Stornæs,Annett Victoria; Pensgaard,Anne Marte (Open Access Journal of Sports Medicine, 2018)
Jan H Rosenvinge,1 Jorunn Sundgot-Borgen,2 Gunn Pettersen,3 Marianne Martinsen,4 Annett Victoria Stornæs,2 Anne Marte Pensgaard5 1Department of Psychology, Faculty of Health Sciences, UiT – The Arctic University of Norway, Tromsø, Norway; 2Department of Sports Medicine, Norwegian School of Sport Sciences, Oslo, Norway; 3Department of Health and Caring Sciences, Faculty of Health Sciences, University of Tromsø, Tromsø, Norway; 4Department of Mathematics, Natural Sciences, and Physical Education, Inland Norway University of Applied Sciences, Hamar, Norway; 5Department of Coaching and Psychology, Norwegian School of Sports Science, Oslo, Norway Introduction: Psychological distress is increasing among adolescents and clusters with other mental health problems such as eating problems. The aim of this study was to investigate the prevalence of psychological distress among young elite athletes and age-matched controls and whether prevalence figures may be attributed to perfectionism and eating problems. Methods: First-year athletes from all Norwegian elite sport high schools (n=711) and 500 students from randomly selected ordinary high schools were eligible for this cross-sectional study. In total, 611 athletes and 355 student controls provided self-report data about psychological distress, perfectionism, and eating problems (ie, body dissatisfaction and a drive for thinness), as well as their physical training/activity. Results: A significantly higher proportion of controls scored above the cutoff point for marked psychological distress. Physical activity above the recommended levels for this age group predicted psychological distress among the controls, while the opposite was found in the student elite athlete sample. In both samples, perfectionistic concerns, ie, concern over mistakes, predicted overall psychological distress. However, among elite athletes, perfectionistic concerns were particularly associated with clinically significant psychological distress. Moreover, the impact of eating problems was ...